Expelled no intelligence allowed - Stein, Ben, 1944-; Craft, Logan; Ruloff, Walt.; Sullivan, John.; Miller, Kevin; Frankowski, Nathan; Premise Media Corporation; Rampant Films; Vivendi Visual Entertainment (Firm) ([Universal City, Calif.] : Vivendi Visual Entertainment, 2008)
Ben Stein travels the world on a quest to learn an awe-inspiring truth - that educators and scientists are being ridiculed, denied tenure, and even fired for merely believing that there might be evidence of 'design' in nature, and that perhaps life is not the result of accidental, random chance, but of intelligent design.
DVD, region 1, widescreen presentation; Dolby Digital, dual layer.
Closed-captioned.
Ben Stein.
Music, Andy Hunter & Robbie Bronniman.
MPAA rating: PG; for thematic material, some disturbing images and brief smoking.
Special features: Talk to Ben; the super-trailer; Christian music; theatrical trailer and TV spots.
Keywords: Intelligent design (Teleology); Educators; Scientists; Evolution -- Religious aspects; Creationism; Intelligent design (Teleology); Educators; Scientists; Evolution -- Religious aspects; Creationism; Video recording for the hearing impaired; Documentary films; Science films; Nonfiction films; Feature films; Video recordings for the hearing impaired; Documentary -- Feature